Kajian perbandingan mitigasi kerentanan fisik, ekonomi, sosial dan lingkungan akibat banjir rob di Demak - Amin, Muhammad (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Disaster vulnerability describes the loss level due to the Rob Flood disaster in Demak Regency through the community's environmental, social, physical, and economic aspects. The research compares physical, economic, social, and environmental vulnerabilities and mitigation strategies to reduce disaster vulnerability. The research method uses a quantitative descriptive approach, strengthened by qualitative data (documents). The research results show that the highest level of vulnerability comes from social and economic vulnerability, followed by physical vulnerability. Only environmental vulnerability has the lowest value compared to the other three aspects. It shows that the Demak government's efforts to build sea walls or embankments reduce vulnerability to tidal flood disasters. Social policy mitigation strategies through reducing population growth rates, providing direct cash assistance, and providing employment opportunities for women and vulnerable groups need more attention to be improved. Economic policies that help people in the agricultural sector, such as assistance with agricultural equipment, assistance with seeds or construction of barns, and training for farmers, still need to be optimized.